Relasi Intelektual Mazhab Basrah dan Kufah dalam Pembentukan Ilmu Nahwu: Analisis Epistemologi - Sundirah Sundirah; Octa Syakila Salsabila; Anis Nurma Sabila; Ba'iq Kurnia Buana (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Arabic grammar as a system of Arabic grammar did not emerge suddenly, but rather developed through a complex intellectual process between the two largest centers of scholarship in the 2nd century AH, namely Basrah and Kufah. This study aims to analyze the intellectual relationship between the Basrah School and the Kufah School in the formation of Arabic grammar from an epistemological perspective. This study uses a qualitative approach with a literature review. The data sources in this study include classical works of Arabic grammar that represent the views and methods of the Basrah and Kufah schools, as well as historical studies of Arabic grammar, contemporary research, and relevant literature on the philosophy of science. Data were collected through documentation and then analyzed using conceptual and comparative analysis to reveal differences in sources of knowledge. The results show that the Basrah and Kufah schools represent two different epistemic orientations. The Basrah school developed a rational-systematic approach by emphasizing strict selection of linguistic data (al-sama‘) and the use of qiyas as the main instrument of rule generalization. In contrast, the Kufah School developed an empirical approach by giving greater authority to sima’i data and variations in actual language usage. The intellectual relationship between the two schools was dialectical and complementary, thus contributing significantly to the formation of nahwu as a stable, coherent, and responsive scientific discipline.